SOCIAL MEDIA ENGAGEMENT AND ADOLESSCENTS’ READING COMPREHENSION IN SENIOR HIGH SCHOOL - Gizella Taskia Ramadana; Yuri Lolita (Premise: Journal of English Education and Applied Linguistics, 2026)
The rapid incorporation of social media into students’ daily lives has transformed it into a powerful learning medium. This shift raises important questions about its potential impact on their academic performance, especially reading comprehension. This study aims to investigate the correlation between senior high school students’ engagement with social media platforms –Instagram, TikTok, and YouTube –and their reading comprehension. A quantitative correlational research design was employed involving 36 senior high school students. Data were collected using a social media engagement questionnaire measuring behavioral, cognitive, and emotional engagement. Further, the reading comprehension test is conducted, consisting of 25 multiple-choice questions. The data were analyzed using Pearson Product-Moment correlation. The correlation analysis showed a significant positive relationship between social media engagement and reading comprehension, with TikTok showing the strongest correlation (r = .823), followed by YouTube (r = .675), and Instagram (r = .395). The results suggest that social media platforms, especially those providing short and multimodal content, may facilitate students’ reading comprehension.